People's Republic of China-Macao Special Administrative Region : Staff Report for the 2014 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report ;, 2014)
KEY MESSAGES Setting. Discussions took place for the first time since the handover of Macao SAR from Portugal to China in 1999. Prudent macroeconomic management has underpinned rapid development in the territory, which is now the world's largest gaming center. As a small, open and tourism-dependent economy, Macao SAR is currently also benefiting from loose global monetary conditions and a Mainland-related boom. Outlook and risks. Growth should stay strong over the next few years at 8-10 percent buoyed by gaming exports and investment, with inflation remaining around 5-5 1\2 percent. However, the economy is vulnerable to external shocks, in particular a slowdown in tourism, due to shocks in the Mainland or Hong Kong SAR or other setbacks to the global recovery. The buoyant property market could also correct if demand fundamentals shift or interest rates rise abruptly with the withdrawal of unconventional monetary policy abroad. Macroeconomic policies. The policy stance is appropriate, with scope for further tightening of macroprudential policies should property prices continue to rise sharply. If downside risks materialize, targeted fiscal stimulus should be used to buttress growth. In the event of a severe property downturn, some countervailing measures could be cautiously unwound. The currency board is the best arrangement for Macao SAR. Financial stability. Important progress has been made in strengthening financial stability in line with the 2011 FSAP recommendations. Prudential measures should focus on managing potential credit and liquidity risks from a gaming slowdown and the property sector, as well as spillovers from shocks in the Mainland and Hong Kong SAR. Longer term challenges. Looking further ahead, Macao SAR's public finances face a moderation in gaming revenues juxtaposed against spending needs from population aging. A sovereign wealth fund to manage part of the territory's fiscal reserves and medium-term budgeting could therefore be useful. As the gaming sector matures, economic diversification toward other services will be key for stable growth.